Reemergence of Blenderized Tube Feedings: Exploring the Evidence. (December 2016) - Bobo, Elizabeth
A blenderized tube feeding (BTF) is a mixture of food and liquid that is pureed and administered through a feeding tube. This method of providing nourishment has been used for millenniums. In fact, it could be viewed as the original form of nutrition support. However, over time, the role of BTF has changed. Initially, it was the only method of nourishing a patient who could not sustain himself or herself on oral feeds. With the development of commercial formulas in the mid-20th century, the usage of this feeding modality declined drastically due to the nutrition precision, ease, and sterility of commercial formulas. Recently, there has been a reemergence in blenderized tube feeds, largely due to patient/family request. The modern perception is that BTF is more natural because the nutrition is coming from whole foods and is able to be varied, as it would be in an oral diet. There are also reports of improved feeding tolerance, such as a reduction in constipation and gagging/retching. However, concerns also exist, such as contamination of the blend with microorganisms and increased viscosity causing feeding tube occlusion. This review summarizes key historical points of the diet, discusses the rationale for use, describes points to consider when using a blenderized diet, and reviews the evidence in practice.